The activity of pyrazolo[4,3-e][1,2,4]triazine and pyrazolo[4,3-e]tetrazolo[1,5-b][1,2,4]triazine sulphonamide derivatives in monolayer and spheroid breast cancer cell cultures - Anna Szymanowska; Dominika Radomska; Robert Czarnomysy; Mariusz Mojzych; Katarzyna Kotwica-Mojzych; Krzysztof Bielawski; Anna Bielawska (Taylor & Francis Group, 2024)
AbstractIn the last decade, an increasing interest in compounds containing pyrazolo[4,3-e][1,2,4]triazine moiety is observed. Therefore, the aim of the research was to synthesise a novel sulphonyl pyrazolo[4,3-e][1,2,4]triazines (2a, 2b) and pyrazolo[4,3-e]tetrazolo[1,5-b][1,2,4]triazine sulphonamide derivatives (3a, 3b) to assess their anticancer activity. The MTT assay showed that 2a, 2b, 3a, 3b have stronger cytotoxic activity than cisplatin in both breast cancer cells (MCF-7 and MDA-MB-231) and exhibited weaker effect on normal breast cells (MCF-10A). The obtained results showed that the most active compound 3b increased apoptosis via caspase 9, caspase 8, and caspase 3/7. It is worth to note that compound 3b suppressed NF-κB expression and promoted p53, Bax, and ROS which play important role in activation of apoptosis. Moreover, our results confirmed that compound 3b triggers autophagy through increased formation of autophagosomes, expression of beclin-1 and mTOR inhibition. Thus, our study defines a possible mechanism underlying 3b-induced anti-cancer activity against breast cancer cell lines.